Propuesta de mejoramiento de líquido refrigerante automotriz fabricado por la empresa Ecoquímicos (2017)
Within the following degree work the main objective was to develop the proposal for improvement of the production of automotive refrigerant liquid manufactured by Ecoquímicos. To meet this objective, the following specific objectives were established: to determine the physical and chemical characteristics of the components used in the automotive coolant manufacturing process; Evaluate alternatives for improvement in the production of automotive coolant and develop the cost analysis of the project in the development of automotive coolant.